Taksonometryczne podstawy kalibracji w statystyce małych obszarów - Paradysz, Jan; Szymkowiak, Marcin (Clustering Methods of Calibration in Small Area Estimation, 2008)
The main goal of the paper is to apply calibration estimators and small area estimation methodology in Household Budget Survey (HBS) in Poland. In Polish HBS non-participation of the households selected for HBS is a very significant problem. In the paper the authors showes how new methodology of calibration and small area estimation in the context of clustering can be used in order to avoid negative impact of nonresponse. The results using calibration and synthetic estimators were also compared with results obtained with using Horvitz-Thompson estimator.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 215-222